2018
DOI: 10.1108/jedt-03-2018-0042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vehicle lightweighting to reduce greenhouse gas emissions with focus on magnesium substitution

Abstract: Vehicle weight reduction represents a viable means of meeting tougher regulatory requirements designed to reduce fuel consumption and control greenhouse gas emissions. This research presents an empirical and comparative analysis of lightweight magnesium (Mg) materials used to replace conventional steel in passenger vehicles with internal combustion engines. The very low density of Mg makes it a viable material for light weighting given that it 1/3 lighter than aluminium and 3/4 lighter than steel. Approach: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…From the other side, the fuel consumption is reduced also if we use aluminum as a lighter material for designing of vehicles, engines and equipment. In that case, the main problem is lower hardness of material resulting in intense wear during tribological contact [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…From the other side, the fuel consumption is reduced also if we use aluminum as a lighter material for designing of vehicles, engines and equipment. In that case, the main problem is lower hardness of material resulting in intense wear during tribological contact [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Even though sufficient knowledge, technology, and available wind speed are necessary to be successful, it seems crucial for developing nations to provide and scrutinize schemes to embark on applying this energy resource. By virtue of using wind energy like other renewable and clean energies, major issues like environmental pollution and global warming, which have caused serious damages to the environment, can be mitigated (Mostafaeipour et al, 2019a;Kulkarni et al, 2018). On the other hand, reduction in fossil fuel sources and their negative effects on the environment make scientists conduct research on renewable resources of energy (Mostafaeipour et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…The critical environment challenge for the human being is of great climate warm effects due to the increasing global carbon dioxide emission. To greatly cut down the emission has been considered as an important international development policy 1,2 . United Nations Environment Program (UNEP) revealed that the building energy consumption has a ratio of 30%‐40% to the total energy consumption and its greenhouse gas emissions will reach up to around 30% by 2030 3 .…”
Section: Introductionmentioning
confidence: 99%